Roadmap on plasmonics. (9th March 2018) - Stockman, Mark I; Kneipp, Katrin; Bozhevolnyi, Sergey I; Saha, Soham; Dutta, Aveek; Ndukaife, Justus; Kinsey, Nathaniel; Reddy, Harsha; Guler, Urcan; Shalaev, Vladimir M; Boltasseva, Alexandra; Gholipour, Behrad; et al.
Abstract: Plasmonics is a rapidly developing field at the boundary of physical optics and condensed matter physics. It studies phenomena induced by and associated with surface plasmons—elementary polar excitations bound to surfaces and interfaces of good nanostructured metals. This Roadmap is written collectively by prominent researchers in the field of plasmonics. It encompasses selected aspects of nanoplasmonics. Among them are fundamental aspects, such as quantum plasmonics based on the quantum-mechanical properties of both the underlying materials and the plasmons themselves (such as their quantum generator, spaser), plasmonics in novel materials, ultrafast (attosecond) nanoplasmonics, etc. Selected applications of nanoplasmonics are also reflected in this Roadmap, in particular, plasmonic waveguiding, practical applications of plasmonics enabled by novel materials, thermo-plasmonics, plasmonic-induced photochemistry and photo-catalysis. This Roadmap is a concise but authoritative overview of modern plasmonics. It will be of interest to a wide audience of both fundamental physicists and chemists, as well as applied scientists and engineers.